Characteristics of Pumice from Cicurug and Its Application as a Bleacher for Crude Palm Oil - Haryono; Atiek Rostika Noviyanti; Hersandy Dayu Kusuma; Irwan Kurnia (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
Pumice is relatively abundant in Indonesia, especially in Cicurug District, Sukabumi. Pumice has unique characteristics, so it has the potential to be an alternative bleaching agent or a bleacher for crude palm oil. Bleaching is one of the stages in processing crude palm oil into palm cooking oil. In the cooking oil industry, the bleaching of crude palm oil generally uses bentonite as a bleacher. This research aims to determine the characteristics of pumice and the optimum conditions for the bleaching process of crude palm oil with pumice as a bleacher. The research method consists of pumice activation, activated pumice characterization, degumming of crude palm oil, bleaching of crude palm oil, and analysis of processed palm oil. The results show that the metal oxide composition in activated pumice is dominated by silica (62.99%) and alumina (14.79%) and has a non-uniform pore size distribution. Optimum bleaching conditions are achieved when using 30% pumice and a bleaching temperature of 105 oC for 30 minutes. Under optimal bleaching conditions, pumice can reduce the color brightness level of crude palm oil from 600 to 125 mg/L Pt, or a bleaching power of 79.2%.